The Exploitation of Nanotechnology in Herbicides and Bioherbicides: A Novel Approach for Sustainable Weed Management - Mirko La Iacona; Aurelio Scavo; Sara Lombardo; Giovanni Mauromicale (Agronomy)
The growing global demand for food security requires a paradigm shift towards sustainable agricultural practices, particularly in weed management. Nanotechnology is emerging in agriculture as a useful tool to reduce the dosage and the negative effects of herbicides on the one side and to improve the bioherbicides efficiency on the other side. This review provides an in-depth analysis of the literature available on the topic, with particular reference to the main characteristics of nanoparticles for weed control and the main nanoformulations for herbicides and bioherbicides. Nanoformulations such as nanoemulsions, nanocapsules, nanospheres, silver nanoparticles and organic materials protect the active ingredients from environmental degradation and enable their controlled release, enhance foliar adhesion and facilitate the penetration into plant tissues while at the same time minimizing the off-target effects. The last paragraph reviews the recent advancements in the field of nanobioherbicides. Moreover, examples of nanoherbicide and nanobioherbicide application in laboratory, greenhouse and field conditions are collected and discussed. This review highlights the increasing efficiency and diffusion of nanoherbicides and nanobioherbicides, suggesting their introduction into sustainable and integrated weed management strategies. However, further research is still required to assess their effectiveness under natural conditions, improve their stability over time and study their bioaccumulation and toxicity toward non-target organisms.